PEMILIHAN SKRIPSI MAHASISWA TERBAIK MENGGUNAKAN METODE COMPOSITE PERFORMANCE INDEX (CPI) - Muryono, Tupan Tri; Sudaryana, I Ketut; Irwansyah, Irwansyah (ISTEK WIDURI, 2021)
Thesis is a scientific work written by undergraduate students that discusses a particular topic or field based on the results of a literature review written by experts, the results of field research, or the results of development (experiments). The problem in this research is that the process of selecting the best thesis is still subjective without regard to other criteria and is also done manually which makes the selection process less efficient. The purpose of this research is to create a system for selecting the best student thesis. The method used in this research is the Composite Performance Index (CPI). Methods of data collection techniques by means of observation, interviews, documentation. The results of this study are the Composite Performance Index (CPI) method can be used for selecting the best student thesis and the results obtained for the first rank are A1 with a value of 218.75, the second rank is A2 with a value of 198.75 and the third rank is A4 with a value of 178.75.